Clinical characteristics of SARS-CoV-2 Omicron pneumonia in immunocompromised and immunocompetent patients: A retrospective cohort study - Xiaoyan Li; Lijuan Li (Heliyon)
Objective: Previous studies evaluating the differences in COVID-19 mortality rates between immunocompromised patients and other patient groups have shown conflicting findings. This research aimed to compare the mortality rates of immunocompromised and immunocompetent patients during the Omicron-dominant period of the SARS-CoV-2 pandemic, and to identify factors associated with prognosis. Methods: We conducted a retrospective analysis of 1085 adult patients (aged ≥18 years) admitted with COVID-19 pneumonia to the China-Japan Friendship Hospital between December 1, 2022, and January 31, 2023. We assessed the prevalence of comorbidities, incidence of co-infections and nosocomial infections, and 30-day mortality. Results: Among the 1085 patients, 254 were immunocompromised, and 831 were immunocompetent. Immunocompromised patients had higher rates of non-invasive ventilation use (30.3 % vs. 21.1 %), invasive ventilation (12.2 % vs. 5.3 %), and 30-day mortality (19.7 % vs. 13.7 %) compared to immunocompetent patients. However, overall mortality rates did not significantly differ based on immunocompromised status. Cox regression analysis identified that elevated troponin T (≥0.15 ng/mL), respiratory failure, high lactate dehydrogenase (≥272.5 U/L), elevated D-dimer (≥1.295 mg/L), increased C-reactive protein (≥90 mg/L), elevated interleukin-6 (>11.67 ng/L), high peripheral blood neutrophil count (>9.84 × 10⁹/L), and immunocompromised status were independent predictors of poor COVID-19 prognosis. In the immunocompetent group, current smoking and a history of interstitial lung disease were related to a worse prognosis. Conclusions: COVID-19 pneumonia due to the Omicron variant may lead to worse outcomes in immunocompromised patients. In immunocompetent patients, careful monitoring is essential for those with respiratory failure, smoking history, or interstitial lung disease to prevent adverse outcomes.